Keefektifan Program Kampus Mengajar Terhadap Peningkatan Literasi dan Numerasi Siswa Kelas VIII SMP Negeri 40 Padang - Rahim, Hamidah; Suryani, Nidia (Indonesian Research Journal on Education, 2022)
The Teaching Campus Program is one of the Independent Learning programs from the Ministry of Education and Culture by targets elementary schools in the 3T area and affected by the COVID-19 pandemic. This program presents students as part of strengthening learning focused on student literacy and numeracy. This study aims to test the effectiveness of the campus teaching program. It focused on research class VIII in 10 students as the experimental class. This research uses an experimental method and this type of research uses a pre-experimental design. Data collection techniques using tests and documentation. Data analysis uses the N-gain test to see whether this program is effective. Based on the analysis results from the calculation of the N-gain score test, it shows that the average value of the N-gain score for experimentation in Indonesian subjects is 79.1389 or 79%, Mathematics is 68.6505 or 69%, and Science is 71.9307. From the results, it can be concluded that the achievement of increasing student literacy has an effective impact, while student numeracy only has a moderately effective impact, which as a whole can be interpreted that the campus teaching program at Junior high school 40 Padang has a fairly effective level of effectiveness.